An German Short-Version of the “Sensory Perception Quotient” for Adults With Autism Spectrum Disorder - Klein, Christoph; Miczuga, Teresa; Kost, Marie Sophie; Röring, Hannah; Jarczok, Tomasz A.; Bast, Nico; Thiemann, Ulf; Fleischhaker, Christian; Tebartz Van Elst, Ludger; Riedel, Andreas; Biscaldi, Monica (Frontiers in Psychiatry, 2022)
Sensory features in autism spectrum disorder (ASD) have received increasing interest in clinical work and research during the recent years. With the Sensory Perception Quotient (SPQ), Tavasolli and colleagues have produced a self-rating scale for adults with ASD that measures sensory hyper-sensitivity in different sensory modalities, without also tapping cognitive or motivational aspects that precede or follow autistic sensory experiences. Here, we present the results of a translation of the SPQ to German and its short version as well as their validation in samples of autistic or neuro-typical participants. We, furthermore, present the psychometric properties and validities of Tavasolli’s original SPQ-short version as well as an alternative short version based on different psychometric item-selection criteria. We can show here that our alternative SPQ-short version, overlapping with the original short-version in 61% of its items, exhibits superior reliabilities, reasonable concurrent validities with other related measures. It, furthermore, exhibits excellent differentiation between autistic and non-autistic samples, underscoring its utility as a screening instrument in research and a clinical instrument to supplement the ASD diagnostic process.